Linguistic annotation of texts in the Uzbek Language Corpora - Samatboyeva, Madina (The Lingua Spectrum, 2025)
This article provides a comprehensive overview of the theoretical and practical foundations of linguistic annotation of the Uzbek language corpus. Within the framework of corpus linguistics, it analyzes the processes of morphological, syntactic, and semantic annotation of texts, their significance for linguistic research, and their contribution to automated language analysis based on corpora. In particular, the development methods of linguistic annotation components – morphological analysis (identifying word forms and grammatical features), syntactic analysis (determining grammatical relationships between words), and semantic annotation (indicating the semantic relationships of words and phrases) – as well as the modern technologies used in their implementation are discussed. The article also examines standardized frameworks widely recognized in the field of natural language processing, especially formats such as Universal Dependencies (UD), analyzing their adaptation and practical application for the Uzbek language. The implementation of the UD formalism in Uzbek is illustrated through examples, and the results of analyses conducted on annotated corpus texts are presented in form. This study contributes to the in-depth exploration and analysis of the Uzbek language as a digital linguistic resource and highlights the scientific and practical significance of linguistic annotation.